Top ten priorities identified by healthcare professionals to support the clinical care of individuals with attention-deficit/hyperactivity disorder: A Canadian Delphi study - Ariana Walji; Debra A. Butt; Emma A. Climie; Penny Corkum; Lily Hechtman; Anne-Claude V. Bedard; Yuanyuan Jiang; Natalie Grizenko; Stacey D. Espinet; Carlin J. Miller; Maria A. Rogers; Maggie E. Toplak; et al. (PLoS ONE, 2025)
Background Limited research exists on key issues that healthcare professionals perceive as important for optimizing Attention-Deficit/Hyperactivity Disorder (ADHD) care. This study identified the top ten priorities that healthcare professionals consider vital to support ADHD care in Canada. Methods A three-round online Delphi study was conducted using electronic surveys from 2022–2024 across Canada. In Round 1, healthcare professionals were asked to rate 21 predetermined items using a 5-point Likert scale and re-evaluated those rankings in Round 2. In Round 2, a new set of 34 items identified from Round 1 were rated and the rankings re-evaluated in Round 3. Consensus was determined by percentage agreement ≥ 90% with a Likert score ≥ 4. For each priority item, the mean Likert score, standard deviation, 95% confidence interval (CI), and the minimum and maximum Likert scores were calculated. Results 96 Canadian healthcare professionals completed Round 1. 82 (85% response rate) completed Round 2 and 73 (89% response rate) completed Round 3. The two highest ranked priorities that achieved 100% consensus agreement were: providing access to well-trained healthcare providers in ADHD (mean score 4.74, 95% CI 4.65–4.84) and access to ADHD-related services (mean score 4.50, 95% CI 4.39–4.61). Among the top ten consensus-derived items, the highest frequency pertained to providing access to healthcare experts in ADHD and related-services (50%) followed by research into ADHD on socio-emotional functioning, co-existing conditions and in diagnosing ADHD in females (30%). Increasing knowledge and educating healthcare professionals and school systems on ADHD was also identified among the top ten priorities (20%). Conclusions Healthcare professionals identified ten top priorities by consensus where most focused on providing access to trained healthcare providers and services to support ADHD care in Canada. Implementing strategies to improve access on a national level will improve the quality of life for individuals living with ADHD.